Respuesta :

Answer:

y = -2(x-2) (x+8)

Step-by-step explanation:

got you bro

leena

Answer:

y = -2x² -12x + 32.

Step-by-step explanation:

Recall that a quadratic equation in standard form is:

y = ax² + bx + c.

To rewrite the equation in standard form, you will need to FOIL and distribute the -2. This can be done by:

y = -2(x-2)(x+8)

FOIL the factored part of the equation. Ignore the '-2' for now.

y = -2 (x² +6x -16)

Now, multiply the '-2' with all of the terms:

y = -2x² -12x + 32.

This is your equation in standard form!

ACCESS MORE